Genetic evidence for involvement of neuronally expressed S1P1 receptor in nociceptor sensitization and inflammatory pain = Genetic evidence for involvement of neuronally expressed S1P 1 receptor in nociceptor sensitization and inflammatory pain - Mair, Norbert; Benetti, Camilla; Andratsch, Manfred; Leitner, Michael G.; Constantin, Cristina E.; Camprubí-Robles, Maria; Quarta, Serena; Biasio, Wolfgang; Kuner, Rohini; Gibbins, Ian L.; Kress, Michaela; Haberberger, Rainer V. (PLOS ONE, 2011)
Sphingosine-1-phosphate (S1P) is a key regulator of immune response. Immune cells, epithelia and blood cells generate high levels of S1P in inflamed tissue. However, it is not known if S1P acts on the endings of nociceptive neurons, thereby contributing to the generation of inflammatory pain. We found that the S1P1 receptor for S1P is expressed in subpopulations of sensory neurons including nociceptors. Both S1P and agonists at the S1P1 receptor induced hypersensitivity to noxious thermal stimulation in vitro and in vivo. S1P-induced hypersensitivity was strongly attenuated in mice lacking TRPV1 channels. S1P and inflammation-induced hypersensitivity was significantly reduced in mice with a conditional nociceptor-specific deletion of the S1P1 receptor. Our data show that neuronally expressed S1P1 receptors play a significant role in regulating nociceptor function and that S1P/S1P1 signaling may be a key player in the onset of thermal hypersensitivity and hyperalgesia associated with inflammation.
Im Titel ist die 2. Zahl 1 tiefgestellt
Gesehen am 09.08.2022